2012
DOI: 10.1177/0266242612459534
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for superior performance under adverse conditions: A focus on small and medium-sized high-growth firms

Abstract: This article explores the strategies pursued by small and medium-sized firms to actively sustain growth within declining markets. A critical analysis of relevant growth theories informs the development of a semi-structured interview schedule; findings drawn from 20 case studies indicate that firms adopt a multiple-strategy approach in which they simultaneously pursue an innovative differentiation and product or service-customisation strategy. Following this strategy, it was found that firms make an intentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 78 publications
3
89
1
9
Order By: Relevance
“…(Hotel,9 employees) The interaction effects of the EO-performance relationship with firm size showed that the positive effect of Proactiveness particularly on financial performance is hampered by micro firm size. This finding indicates that despite the flexibility originating from their small size (Bamiatzi & Kirchmaier, 2014;Getz & Carlsen, 2000), micro firms might face difficulties in either implementing proactive efforts due to limited workforce, expected margins, or that they simply do not have the financial means to exploit these proactive capabilities (Weiermair & Peters, 1998). Drawing on the literature of social networks in tourism and the regional embeddedness of tourism family firms (Peters & Kallmuenzer, 2015;Strobl & Peters, 2013), one can find that microsized rural tourism family businesses use their networks and social ties to cooperate (Chrisman et al, 2015;Glover & Reay, 2015) and overcome their size disadvantage (Harms, Memili, & Steeger, 2015;Sundbo et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…(Hotel,9 employees) The interaction effects of the EO-performance relationship with firm size showed that the positive effect of Proactiveness particularly on financial performance is hampered by micro firm size. This finding indicates that despite the flexibility originating from their small size (Bamiatzi & Kirchmaier, 2014;Getz & Carlsen, 2000), micro firms might face difficulties in either implementing proactive efforts due to limited workforce, expected margins, or that they simply do not have the financial means to exploit these proactive capabilities (Weiermair & Peters, 1998). Drawing on the literature of social networks in tourism and the regional embeddedness of tourism family firms (Peters & Kallmuenzer, 2015;Strobl & Peters, 2013), one can find that microsized rural tourism family businesses use their networks and social ties to cooperate (Chrisman et al, 2015;Glover & Reay, 2015) and overcome their size disadvantage (Harms, Memili, & Steeger, 2015;Sundbo et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…Larger (family) firms are also usually more able to endure financial crises (Lee, 2006) due to greater financial endowment. At the same time, small firms can benefit from more flexible business behaviour, such as being able to quickly react to environmental changes or by focusing on niche strategies (Bamiatzi & Kirchmaier, 2014). To conclude, previous findings lead to the hypothesis that firm size negatively affects the implementation of EO in rural tourism family firms, as micro firm size potentially blocks an effective exploitation of innovative, proactive and risk-taking efforts due to restrictions in capital and workforce.…”
Section: Hypotheses Developmentmentioning
confidence: 77%
See 3 more Smart Citations